2011
DOI: 10.1055/s-0031-1281867
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Volumetric Spatially Angle-Corrected Pixelwise Fetal Flow Volume Measurement

Abstract: Spatial angle-corrected global fetal perfusion measurement improves existing approaches to fetal perfusion evaluation, and is feasible, simple and fast. Thus, it can be recommended to explore the relationship of fetal perfusion and disturbances of fetal development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The pixelwise evaluation of blood flow in a variety of tissues and organs, in man and animals, has demonstrated highly significant correlation to relevant physiological (oxygenation) and pathophysiological (histological changes in rejection, fibrosis and inflammation as well as diabetic changes of microperfusion) parameters, and perfusion changes in the female genital tract. 3D fetal perfusion volume measurements have the potential to describe fetal perfusion very precisely. In contrast to traditional PI, RI and flow velocity measurements, the novel flow volume measurements reflect the fetal supply of blood more precisely since a certain quantity of blood is necessary to transport certain amounts of oxygen and nutrients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pixelwise evaluation of blood flow in a variety of tissues and organs, in man and animals, has demonstrated highly significant correlation to relevant physiological (oxygenation) and pathophysiological (histological changes in rejection, fibrosis and inflammation as well as diabetic changes of microperfusion) parameters, and perfusion changes in the female genital tract. 3D fetal perfusion volume measurements have the potential to describe fetal perfusion very precisely. In contrast to traditional PI, RI and flow velocity measurements, the novel flow volume measurements reflect the fetal supply of blood more precisely since a certain quantity of blood is necessary to transport certain amounts of oxygen and nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…More relevant than arterial flow velocity changes is the total amount of blood transported through the umbilical vein towards the fetus. The PixelFlux technique allows such three‐dimensional (3D) perfusion volume measurement in the umbilical vein. The first report described its use to differentiate normal fetuses from those with intrauterine growth restriction (IUGR).…”
Section: Introductionmentioning
confidence: 99%
“…The machine we used is widely but not universally used. Two solutions to this drawback are possible: 1. to calibrate the machine settings with a flow phantom: we developed a flow phantom and could demonstrate a highly significant correlation of PXFX measurements with a direct flow volume measurement [31] and with laser Doppler measurements (data not shown);…”
Section: Cortical Tissue Perfusion Intensitymentioning
confidence: 99%
“…1a/b demonstrates the principle of this pixel flow analysis (PFA) tool compared to the established PW-Doppler. PFA has already been evaluated for placenta vascularization, umbilical cord flow during pregnancy, and in an experimental setting to detect ischemic lesions in testicular torsion in rats, with promising results 20 21 22 23 . Furthermore, a phantom study showed a good correlation of the actual flow recorded with PFA using a plastic tube with a predefined flow volume 22 .…”
Section: Introductionmentioning
confidence: 99%